Edukasi Pedoman Gizi Seimbang dan Implementasi Isi Piring Makanku pada Siswa SMP Negeri 5 Kota Jambi - Aisah Aisah; Aidil Havis (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Knowledge of nutrition is one of the indirect causes of malnutrition. Increasing knowledge through nutrition education can prevent malnutrition and improve a person's behavior to consume food according to their nutritional needs. Good knowledge is one of the factors that influence a person's attitude and behavior. Health promotion activities are carried out to provide knowledge about health and ultimately to prevent health problems. The purpose of community service activities is to provide or increase knowledge and understanding of students of SMP Negeri 5 Jambi City regarding guidelines for balanced nutrition and the implementation of the contents of my eat plate. Counseling is an effort to change human behavior through an educative approach. Based on the results of an initial survey conducted at SMP Negeri 5 Jambi City in Juli 2022, it was found that students' functional nutritional literacy regarding balanced nutrition was still low. Only 19% of students who have good functional nutritional literacy. The solution offered is nutrition education about balanced nutrition guidelines that can increase students' knowledge and implementation of